ORGANIZATIONAL COMMITMENT WITH QUALITY OF NURSING IN THE RSI SAKINAH MOJOKERTO - Abdul Muhith; Indira Yulias Wihannusa; Siti Nur Hasina; Imamatul Faizah; Ratna Yunita Sari (Nurse and Health: Jurnal Keperawatan, 2022)
Background: Good service quality not only measures the luxury of the facility, but from employee behavior and behavior should reflect high professionalism and commitment. Objectives: The purpose of this study was to determine the relationship between Organizational Commitment with Quality of Nursing Service in Inpatient Room of the RSI Sakinah Mojokerto. Methods: This research used Cross Sectional approach. The population of all nurses in the Inpatient Room of the RSI Sakinah Mojokerto, who spoke 85 nurses. Technique Sampling used in this study was Total Sampling and obtained by sample counted 85 respondents. The data source used the primary data obtained through the questionnaire. Data analysis was using the Spearman Rank Test. Results: The results of this study were obtained almost entirely (76.5%) Organizational Commitment in Inpatient Room of RSI Sakinah Mojokerto included in the category of High Organizational Commitment. Nursing Care Quality (Nursing Care Standards and Professional Performance Standards Nurses) at the RSI Sakinah Mojokerto Inpatient Hospital RSI was almost entirely included in the good category. The result of Spearman Rank test statistic with sig level (.05), got correlation value .000 (< .05) meaning that there was a correlation of Organization Commitment with Nursing Care Quality (Nursing Care Standard and Professional Performance Standard of Nurse) at Inpatient Room of the RSI Sakinah Mojokerto. Conclusion: The task of the hospital as a health service institution was to improve the skills, speed, ease and accuracy in conducting the practice of nursing health services and more responsible in providing services so as to maintain commitment to the organization.